Pulmonary Vein Varix: A Diagnostic Enigma - Howdekar, Madhuri; Susarla, Rammurti; Mutnuru, Phani Chakravarty; GK, Paramjyothi; Kalva, Sanjeeva Prasad (Journal of Clinical Interventional Radiology ISVIR, 2023)
We report a case of a 34-year-old woman who presented with chest pain, shortness of breath, and dry cough of 1 month duration. Contrast-enhanced computed tomography of the chest revealed an enlarged and tortuous right pulmonary vein that could not conclusively exclude a pulmonary arteriovenous malformation. Further evaluation with digital subtraction angiography excluded an arteriovenous malformation and confirmed the presence of a pulmonary vein varix. Accordingly, the patient was managed conservatively. This report highlights the need for catheter angiography in the diagnosis of pulmonary vein varix and provides a brief review of literature on the entity.
Keywords: pulmonary vein varix; rare pulmonary vascular anomaly; pulmonary vein varix